Synergy of Financial Technology and Intellectual Capital in Strengthening Banking Financial Performance in the Era of Digital Transformation - Masriani. H; Tamrin Meda; Sitti Zuhriyah (Poltanesa, 2026)
Abstract— This study aims to analyze the effect of financial technology on banking financial performance and examine the moderating role of intellectual capital in strengthening this relationship in the Indonesian banking industry. The study applies a quantitative approach using explanatory research with panel data analysis. The research sample consists of 15 state-owned and private commercial banks listed on the Indonesia Stock Exchange during the 2021–2024 period, resulting in 60 panel observations. Financial performance is proxied by Return on Assets (ROA), financial technology is measured using the Fintech Index through the Weighted Fintech Disclosure Index (WFDI), while intellectual capital is proxied by Value Added Intellectual Coefficient (VAIC). Data analysis employs panel data regression and Moderated Regression Analysis (MRA) using EViews 14 software. The results indicate that financial technology has a significant effect on financial performance, although the relationship shows a negative direction in the short term due to high digital transformation investment costs and operational adjustments. Furthermore, intellectual capital is proven to strengthen the relationship between financial technology and financial performance. These findings imply that the effectiveness of digital transformation in the banking sector is not solely determined by technology adoption, but also by the company’s ability to manage knowledge, innovation, and human resource competencies effectively. This study extends the Resource-Based View Theory by emphasizing the strategic synergy between digital technology and intellectual capital in improving banking competitiveness and financial sustainability in the digital transformation era.